Impact of self-care programs in Type 2 Diabetes Mellitus population in primary health care. Systematic review and meta-analysis - Caro-Bautista, Jorge; Kaknani-Uttumchandani, Shakira; García-Mayor, Silvia; Villa-Estrada, Francisca; León-Campos, Álvaro; Gómez-González, Alberto (Wiley, 2020)
Aims and Objectives: To evaluate the effectiveness of self-care programs in type 2 diabetes mellitus (T2DM) population in primary health care. Design : Systematic review and meta-analysis. Methods: A search was conducted in PubMed, CINAHL, WOS and Cochrane databases for randomised controlled trials carried out in the period January 2005-December 2017, including studies with at least one face-to-face educational interventions. The quality of the evidence for the primary outcome was evaluated using the GRADE System. A meta-analysis was used to determine the effect achieved although only the results classified as critical or important were taken into consideration. Checklist of Preferred Reporting Items for Systematic Reviews and Meta-analyses has been followed. PROSPERO registration Number: CRD42016038833. Results: In total, 21 papers (20 studies) were analysed, representing a population of 12,018 persons with T2DM. For the primary outcome, HbA1c, the overall reduction obtained was - 0.29%, decreasing the effect in long-term follow-up. The quality of the evidence was low/very low due to very serious risk of bias, inconsistency and indirectness of results. Better results were obtained for individual randomized trials versus cluster designs and in those programs in which nurses leaded the interventions. The findings for other cardiovascular risk factors were inconsistent. Conclusions Educational interventions in primary care addressing T2DM could be effective for metabolic control, but the low quality of the evidence and the lack of measurement of critical results generates uncertainty and highlights the need for high-quality trials. Relevance to clinical practice: Most of self-care programs for T2DM in primary care are focused on metabolic control, while other cardiovascular profile variables with greater impact on mortality, or patient reported outcomes are less intensely addressed.
T2DM self-care programs in primary care
Keywords: Diabetes tipo 2; Type 2 Diabetes Mellitus; meta-analysis; primary health care; self-care; diabetes education